Improving lentil (Lens culinaris) productivity and profitability through farmer participatory action research in India - SINGH, A K; SINGH, A K; MISHRA, ANUPAM; SINGH, LAKHAN; DUBEY, S K (The Indian Journal of Agricultural Sciences, 2016)
Application of technology for on-farm productivity enhancement is the major intervention besides meeting the other requirements like input supply, marketing, biotic and abiotic stresses. Further, to what extent farmers are involved in technology delivery process is another dimension of technology application. Farmers may be either the passive receiver of any technology of information, or they be be the active partners in planning, implementing and evaluating the interventions. In the first phase of the study, documentation and characterization of lentil based cropping systems, variety use pattern and existing yield level; comparison of lentil (Lens culinaris Medik.) and non-lentil based cropping systems, constraint analysis and identification of need based and situation specific potential solutions were done. In the second phase of the study, the suggested solutions were translated and prioritized into meaningful interventions in the form of lentil variety demonstration; assessment of different technological components like weed management,fertilizer Â management, irrigation management and disease management in integrated crop management (ICM) mode and implemented for two cropping seasons of 2010-11 to 2011-12. Action research was, therefore, conducted among 965 lentil growers (389 ha area) selected from 35 districts across four states of India during 2010-11 to 2011-12. Yield gap II (37.65 - 54.39%) was found more prominent than the research gap or yield gap I (15.0 - 22.5 %) in selected states. The states of Uttar Pradesh (716 kg/ha), Bihar (629 kg/ha), Madhya Pradesh (619 kg/ha) and West Bengal (604 kg/ha) showed higher yield gap in lentil. Distinct lentil based existing cropping system and very poor level of yields was observed (as low as 300 kg/ha in Madhya Pradesh to 932 kg/ha in some parts of Uttar Pradesh). Lentil based cropping systems (B: C ratio - 3.11-3.77) was economically efficient than non-lentil based cropping system (B:C ratio - 1.17 to 1.72). Assessment of improved lentil varieties and integrated crop management technologies resulted in higher gain both in yield (57.8%) and net return (87.8%), followed by improved variety (50.4% increase in yield and 82.2% higher net return) over the farmers' practices. Other technological components like weed management, fertilizer management, irrigation management and disease management contributed increase in yield (20-29%) and net returns (17-37%) over farmers' practices.